The association of hypogonadism with depression and its treatments - Indirli, Rita; Lanzi, Valeria; Arosio, Maura; Mantovani, Giovanna; Ferrante, Emanuele (Frontiers in Endocrinology, 2023)
According to World Health Organization estimates, 5% of the adult population worldwide suffers from depression. In addition to the affective, psychomotor and cognitive symptoms which characterize this mood disorder, sexual dysfunction has been frequently reported among men suffering from depression. The most common sexual manifestations are decreased libido, erectile dysfunction and orgasmic disorder. In addition, epidemiological studies have documented a reduction of testosterone concentrations in men with depression and, for these reasons, depressive disorders appear as one possible cause of male functional hypogonadism. Moreover, some largely used antidepressant medications can cause or worsen sexual complaints, thus depression and its treatments rise several andrological-relevant issues. The other way round, men with hypogonadism can manifest depressed mood, anxiety, insomnia, memory impairment which, if mild, may respond to testosterone replacement therapy (TRT). However, the prevalence of functional hypogonadism in depression, and of depressive symptoms in hypogonadal men, is not known. Severe depressive symptoms do not respond to TRT, while the effect of treating major depression on functional hypogonadism, has not been investigated. Overall, the clinical relevance of each condition to the other, as well as the physiopathological underpinnings of their relationship, are still to be clarified. The present review summarizes current evidence on the influence of testosterone on mood and of depression on the hypothalamic-pituitary-testis axis; the clinical association between male hypogonadism and depression; and the reciprocal effects of respective treatments.